Decision Factors Court Constitution Related Results Election President 2024 Against Indonesian Politics and Law - Ismaidar Ismaidar; Tamaulina Br. Sembiring; Raja Arsyadil Fiqry Siregar (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
The Republic of Indonesia is a constitutional state, as specified in Article 1, Paragraph (3) of the 1945 Constitution. As a nation that upholds the rule of law as the highest authority in its governmental system, the existence of the Judiciary plays a central role as an absolute requirement for upholding the supremacy of law to ensure justice. According to the provisions of Article 24, Paragraph (2), the Supreme Court and the Constitutional Court are institutions with the highest authority in enforcing law and justice in accordance with the mandate of the Constitution. The 2024 Indonesian Presidential and Vice-Presidential Election, also known as the 2024 Presidential Election, is the fifth such election in Indonesia to choose the President and Vice President of the Republic of Indonesia. The results of this election triggered various reactions from different groups. Criticism of the results, particularly from opposing candidates, was not uncommon. This debate occurred not only among political elites but also within the broader community. The purpose of this study is to examine the factors influencing the Constitutional Court's decision regarding the results of the 2024 Presidential Election and its impact on Indonesia's political and legal systems. This research employs a normative juridical legal approach, using library research as the primary data source. The study reveals that in resolving disputes over the 2024 Presidential Election results, the Constitutional Court considered valid and relevant evidence, despite dissenting opinions from some judges. The decision's impact-both in terms of the winner's legitimacy and public perception-can either enhance or deteriorate public views on the quality of Indonesia's democracy. This research is expected to provide deeper insights into the role of the Constitutional Court in safeguarding electoral integrity, addressing political controversies, and its implications for Indonesia's future political system.